Analisis Motivasi terhadap Kinerja Guru dengan dengan Kepuasan Kerja sebagai Variabel Intervening (Studi pada Yayasan Taman Pendidikan Rahmat Kota Kediri) - Fadilah Janati (Universitas Islam Kadiri, 2020)
Education quality that expected to be not only for just curiculum target achievement, but also concerning all performance which is support in achieving quality of school education. The implementation facing some problems, like the quality of human resources concerning creativity needs especially teacher creativity to develop education quality in globalization era. Teacher motivation needed in order to achieve teacher performance that expected. Beside that, through work satisfaction also become one of among factors in achieving good teacher performance of Rahmat education foundation, Kediri City. This research purpose is to analyze motivation effect towards teacher’s performance,analyze motivasion effect towards teacher’s performance through work satisfaction at YTP Rahmat, Kediri City.This research uses quantitative method, includes with 85 teachers of Rahmat edducation foundation as respondent. Operational variabels consist of motivation, teacher’s performance and work satisfaction. Using Path Analyze as data analyzing method. Research’s results are direct influence between motivation towards teacher’s performance at rahmat education foundation, Kediri City. (1) The amounts of motivation direct influence towards teacher performance showed in beta standardized value of 0,479 and for the linear regression coefficient of the motivation variable has a positive direction towards teacher’s performance of Rahmat education foundation, Kediri City. (2) Positive influence and significant between motivation towards teacher’s work satisfaction of Rahmat education foundation, Kediri City with the beta standardization coefficient value of 0,723 and significance of 0,00<0,05. (3) There is motivation influence towards teacher’s performance through teacher’s work satisfaction of Rahmat education foundation, Kediri City. The value of direct influence is 0,479 while the value of indirect influence must calculate by diverting indirect coefficient of (0,723) X (0,356)=0,257. Because of direct relation coefficient bigger than indirect relation coefficient the it can be said that the relation among the is direct relaton.